Welfare state reform in Southern Europe : fighting poverty and social exclusion in Italy, Spain, Portugal and Greece - Ferrera, Maurizio (Routledge/EUI studies in the political economy of welfare, 2005)
This new study delivers a detailed analysis of the efforts being made to reduce poverty and social exclusion in Portugal, Spain, Italy and Greece. After an initial discussion of the 'southern model' of the welfare state, the situation of each country is clearly illustrated. This book also discusses how the experience of southern Europe might bear upon the situation of the East European accession countries. This is excellent reading for those interested in social change across Europe and beyond.